Interfacial double-coordination effect reconstructing anode/electrolyte interface for long-term and highly reversible Zn metal anodes - Zhou, Jie; Yu, Huaming; Qing, Piao; Chen, Dongping; Huang, Shaozhen; Jin, Youliang; He, Hanwei; Zhou, Gang; Xie, Zeqiang; Chen, Yuejiao (Journal of colloid and interface science, 2025)
Thiamine hydrochloride (TH) acts as a highly efficient additive to traditional ZnSO4 electrolyte, which combines zincophilic groups and polar groups, in situ reconfiguring the anode/electrolyte interface based on interfacial coordination chemistry, thus enhancing the electroplating/stripping reversibility of Zn metal anodes. [Display omitted] The highly reversible electrochemical deposition and dissolution of zinc metal anode is a critical feature for the practical application of aqueous zinc-ion batteries (ZIBs). Nevertheless, this process is seriously hindered by the uncontrollable electrodeposition and interfacial side reactions caused by thermodynamically unstable anode/electrolyte interface (AEI). Guided by the electrode/electrolyte interface chemistry, thiamine hydrochloride (TH) as a novel additive is added into traditional ZnSO4 (ZS) electrolyte to induce sustained reversible Zn deposition/stripping. Spectroscopic characterizations and electrochemical tests reveal that TH can adsorbed on the anode surface owning to the strong double-coordination effect between N, S atoms and Zn atoms via Zn-N and Zn-S chemical bonds. In addition, there are polar hydroxyl groups in the TH molecular structure which can form hydrogen bonds with water molecules. Thus, the adsorbed TH layer can not only guide the diffusion of Zn2+ ions and achieve dendrite-free electrodeposition process, but also prevent intimate contact between water and anode to suppress the occurrence of interface side reactions. Based on these benefits, the TH additive achieves an ultra-long stable cycle lifespan to 2045 h at 1 mA cm−2 and 1 mAh cm−2. Even at a higher current density of 5 mA cm−2, prolonged cycling performance about 773 h is demonstrated. Besides, the assembled Zn//NVO full cells reveal excellent capacity retention and rate performance under practical conditions, highlighting the efficient and reliable coordination effect of TH additive at the AEI.